2010
DOI: 10.1002/pssa.200925308
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of rapidly annealed Ni/Mo Schottky barriers on n‐type GaN

Abstract: Thermal annealing effects on the electrical and structural properties of Ni/Mo Schottky contacts on n-type GaN have been investigated by current-voltage (I-V), capacitance-voltage (C-V), Secondary ion mass spectrometer (SIMS), and X-ray diffraction (XRD) techniques. The extracted Schottky barrier height (SBH) of the as-deposited contacts was found to be 0.66 eV (I-V), 0.74 eV (C-V). However, both measurements indicate that the barrier height slightly increases when the contacts are annealed at 300 and 400 8C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Accordingly, the consumption of the defect region is followed by an increase in the value of the barrier height calculated from I-V characteristics upon annealing temperature. Similar results were also reported by Wang et al [33], Jyothi et al [21] and Rao et al [34]. Wang et al [33] studied the thermal annealing behaviour of Pt/n-GaN and they observed that the variation of barrier height upon annealing may be attributed to changes of surface morphology and variation of non-stoichiometric defects in the vicinity of the interface.…”
Section: Samplesupporting
confidence: 85%
See 2 more Smart Citations
“…Accordingly, the consumption of the defect region is followed by an increase in the value of the barrier height calculated from I-V characteristics upon annealing temperature. Similar results were also reported by Wang et al [33], Jyothi et al [21] and Rao et al [34]. Wang et al [33] studied the thermal annealing behaviour of Pt/n-GaN and they observed that the variation of barrier height upon annealing may be attributed to changes of surface morphology and variation of non-stoichiometric defects in the vicinity of the interface.…”
Section: Samplesupporting
confidence: 85%
“…They reported that the Ni Schottky contact with a 300 nm thickness shows good rectifying behaviour after annealing at 450 • C during 3 min under Argon. Recently, Jyothi et al [21] studied the electrical and structural characteristics of Ni/Mo Schottky rectifiers on n-GaN in the temperature range 300-600 • C. They reported that the Ni/Mo Schottky rectifier exhibits excellent electrical properties even after annealing at 600 • C. Very recently, Chang et al [22] fabricated GaNbased Schottky barrier photodiode with Ir/Pt metallization scheme. They found that the barrier height increased from 0.91 eV to 1.03 eV and the ideality factor decreased from 1.58 to 1.16 after annealing at 600 • C in O 2 atmosphere.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…14) In particular, the fact that only majority carriers contribute to the rectification process through Schottky barrier implies that the frequency response of the diode is limited only by RC charging or the transit time, rather than by minority carrier lifetime prevailing in conventional p-n diodes. This property makes it particularly suited for high speed switching applications, microwave detection, mixing, harmonic generation and parametric amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, thermal treatment during the fabrication process of Schottky diodes can give significant effects on the electrical properties such as barrier height, ideality factor, and leakage current, resulting in the modification of the device performance. 13,14) Therefore, the detailed knowledge of Schottky contacts under annealing process will be helpful in understanding and controlling electrical properties of Schottky diodes. 15) In the present work, in continuation to our previous work, 12) the authors investigated the effect of rapid thermal annealing (RTA) on the electrical and structural properties of Se Schottky contacts to n-type Si.…”
Section: Introductionmentioning
confidence: 99%